SAT0018 Neurodevelopmental Long Term Outcome in Children Born to Mothers with Systemic Lupus Erythematosus and Antiphospholipid Syndrome. (10th June 2014) - Nalli, C.; Iodice, A.; Andreoli, L.; Lojacono, A.; Motta, M.; Fazzi, E.; Tincani, A.
Abstract : Background: Systemic lupus erythematosus (SLE) is a complex autoimmune disease that primarily affects women in childbearing age. Antiphospholipid Syndrome (APS) is a systemic autoimmune disorder defined by the occurrence of thrombosis and pregnancy morbidity in presence of Antiphospholipid Antibodies (aPL). Experts in the field well know relationship between circulating aPL and neurologic manifestation, thrombotic or not, in APS patients. Less is known about a possible role of aPL in influencing or interfere with the long-term outcome and the neurodevelopmental outcome of children exposed during pregnancy to aPL. In presence of any kind of neurological disorder, however, it's mandatory first of all to exclude a possible role of prematurity and presence of environmental factors, then we can consider a possible pathological role of aPL. Objectives: To evaluate the neurodevelopmental outcome in 35 children (median age 6 years-old) born to mothers with SLE or APS with IgG antiBeta2Glycoprotein I (aB2GPI) positivity during third trimester of pregnancy. All children were IgG-aB2GPI positive at birth (low-medium titers). Methods: A neurological physical exam was performed by a pediatric neurologist in all children. To all APS/SLE mothers are submitted some questionnaires: Child Behavior Check List (CBCL) and an anamnestic home-made set of questions. This in particular was obtained by a multidisciplinary team (rheumatologists and pediatric neurologists) and focusing on maternal drugs during pregnancy, gestational age, baby developmental milestones, scholastic performances. Intellectual functioning were performed with Wechsler scale for corrected age. Results: In all children the neurological physical exam was normal. We found a particular profile in 6 of these children (17%, all at term) in which coexist mild behavior disorders (Attention Deficit Hyperactivity Disorder and mood disorders), sleep disorders (parasomnias) and learning difficulties in the non-verbal domain of functioning. Two children had a history of seizures: one of them was preterm and had neonatal stroke, maybe related to the exposure to high level of maternal aPL during pregnancy. All 35 children showed a normal intelligence level. Conclusions: The results are overall reassuring on a normal intelligence. For the first time was noted a possible relationship between maternal aPL and sleep disorders in children born to SLE and APS patients. In utero exposure to aPL may interfere with the long term outcome of these children, regarding in particular some neurodevelopmental areas. References: Bomba M, Galli J, Nacinovich R, Ceribelli A, Motta M, Lojacono A, Fazzi E, Tincani A. Neuropsychiatric aid in children born to patients with rheumatic diseases. Clin Exp Rheumatol. 2010 Sep-Oct; 28 (5): 767-73. Urowitz MB, Gladman DD, MacKinnon A, Ibañez D, Bruto V, Rovet J, Silverman E. Neurocognitive abnormalities in offspring of mothers with systemic Lupus Erythematosus. Lupus 2008: 17 (6): 555-60. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5324